Policy, Institutional, and Price Determinants of Tourism Competitiveness in Uzbekistan - Bobur Sobirov (Proceedings of The ICECRS, 2025)
General Background The foundational destination-competitiveness literature establishes that an enabling environment—composed of regulatory frameworks, policies, and institutional quality—serves as a core pillar determining how effectively a country can convert its raw resources into visitor value. Specific Background Assessing these structural relationships typically involves comparing overall sector performance against sub-indices tracking business environments, health, environmental sustainability, and price structures. Knowledge Gap However, the relative quantitative weights of these determinants are rarely measured alongside price metrics, and detailed institutional distance-to-frontier benchmarking remains scarce for emerging Central Asian destinations. Aims This study quantifies the association between overall tourism competitiveness and four enabling sub-indices across ten leading global economies and Uzbekistan using 2024 index data. Results The empirical analysis demonstrates that the policy-and-enabling-conditions sub-index is the strongest correlate of overall competitiveness ($r = 0.87$), proving that institutional quality is a first-order determinant. Conversely, Uzbekistan's enabling environment is globally weak, with its business environment ranking 82nd and travel prioritization ranking 68th. Its price competitiveness index ($4.05$) sits far below the global frontier ($6.20$), exposing a strategic price illusion. Novelty This paper introduces a quantitative approach to evaluating the policy-price nexus in Central Asia, challenging the traditional reliance on cost-based advantages. Implications Strategic development architectures must shift away from fragile price-led strategies and prioritize institutional, business environment, and regulatory upgrades that act as multiplier mechanisms for wider infrastructure investments. Keywords Tourism Competitiveness, Institutional Quality, Policy, Price Competitiveness, Uzbekistan Key Findings Highlights The policy and enabling conditions sub-index exhibits the strongest positive correlation with overall destination competitiveness among all evaluated pillars. Distance-to-frontier comparisons reveal that the emerging economy lags behind global benchmark leaders across both general regulatory and sector-specific prioritization metrics. The apparent competitive advantage built on lower prices is an illusion, as the local price index remains significantly below the regional and global frontiers.